The Peroxygenase Activity of the Aspergillus flavus Caleosin, AfPXG, Modulates the Biosynthesis of Aflatoxins and Their Trafficking and Extracellular Secretion via Lipid Droplets - Hanano, Abdulsamie; Alkara, Mari; Almousally, Ibrahem; Shaban, Mouhnad; Rahman, Farzana; Hassan, Mehedi; Murphy, Denis J. (Frontiers in Microbiology, 2018)
Aflatoxins (AF) are highly detrimental to human and animal health. We recently demonstrated that the Aspergillus flavus caleosin, AfPXG, had peroxygenase activity and mediated fungal development and AF accumulation. We now report the characterization of an AfPXG-deficient line using reference strain NRRL3357. The resulting fungal phenotype included a severe decrease in mycelium growth, failure to sporulate, and reduced AF production. Increasing cellular oxidative status by administration of H2O2 and cumene hydroperoxide did not restore the AfPXG-deficient phenotype, which suggests that AfPXG-deficiency is not directly related to oxidative stress. To investigate possible alternative roles of AfPXG, a gain of function approach was used to overexpress AfPXG, with the reporter gene Gfp, in an AfPXG-deficient line, termed AfPXG+. The resulting phenotype included elevated numbers of stable lipid droplets (LDs) plus enhanced AF production. Highly purified LDs from AfPXG+ cultures sequestered AF and this ability was positively correlated with overall LD number. Site-specific mutagenesis of AfPXG to delete Histidine 85 (AfPXGHis85), a residue essential for its catalytic activity, or by deletion of the putative LD targeting domain (AfPXGD126-140), showed that AfPXG-peroxygenase activity was required for AF biosynthesis and that integration of AF into LDs was required for their export via a LD-dependent pathway. Ectopic expression in fungal cells of the plant LD-associated protein, oleosin, also resulted in both additional LD accumulation and enhanced AF secretion. These results suggest that both fungal LDs and their associated caleosin proteins are intimately involved in the biosynthesis, trafficking and secretion of aflatoxins.